Hydrogen Atom and Molecule Adsorptions on FeCrAl (100) Surface: A First-Principle Study - Li, Xiaojing; Ma, Yu; Zhou, Wenzhong; Liu, Zhao (Frontiers in Energy Research, 2021)
FeCrAl alloys are promising accident-tolerant fuel (ATF) cladding materials for applications in light water reactors (LWRs). Despite the excellent mechanical and antioxidation properties, this series of iron-based alloys has poor hydrogen embrittlement (HE) resistance due to the strong hydrogen uptaking ability. The hydrogen embrittlement effect can cause the degradation and premature failure of the material, and this effect can be enhanced by the high-temperature/high-pressure/high-irradiation environment in reactors. So, the potential danger should be taken seriously. In this paper, we have studied the hydrogen atom and molecule adsorptions on both Fe (100) and FeCrAl (100) surfaces to discover how the hydrogen atom and molecule (H/H2) interact with the Fe and FeCrAl (100) surface in the first place. The results show that there are strong element effects on the FeCrAl surface. The Al atom itself has no interaction with hydrogen. When the Al atom is beside the Fe atom, this Fe atom has a slightly lower interaction with hydrogen. However, the Al atom beside the Cr atom will enhance the hydrogen interaction with this Cr atom. On the other hand, when the Cr atom is beside the Fe atom, these two atoms (Fe–Cr bridge site) can reduce the interactions with H. In addition, when two Cr and two Fe atoms together make a four-fold site (FF site), the two Cr atoms can increase the interaction of the two Fe atoms with H. The element effects discovered can be a good guide for making hydrogen prevention coatings.